TRAINING FOR ENHANCEMENT OF STORYTELLING ABILITY FOR PROSPECTIVE ELEMENTARY SCHOOL TEACHERS - Decenni Amelia; Neni Maulidah; Syaffa Resundane (International Journal of Engagement and Empowerment, 2021)
This service activity aims to provide understanding and storytelling training to prospective elementary school teachers to create prospective teachers who are skilled in modifying or using creative learning methods, attracting student learning interest, and improving the storytelling abilities of future elementary school students teachers. The location of this activity is at Bhayangkara University, Greater Jakarta, where the training process is carried out using the Zoom Meeting application due to the Covid-19 pandemic. With the number of participants as many as 25 PGSD students from various agencies or universities. The model used is mentoring or counseling about basic theory and storytelling training. The activity method is synchronous and asynchronous training. The first day of direct face-to-face training is conducted online between the presenters and training participants through zoom meetings, then continued training on the 2nd and 3rd days indirectly (not real-time) between the presenters and training participants. The participants will be given the task of analyzing two storytelling videos. Each participant is asked to make a storytelling work then upload it via the link prepared on G-Drive to be evaluated and given guidance by the team for implementing community service activities. The results of the observations showed positive things. The prospective elementary school teachers (PGSD students) were very enthusiastic about participating in this training activity and were motivated to practice it in learning activities. In addition, participants can produce storytelling works